1984
DOI: 10.1128/iai.43.3.856-859.1984
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Cryptosporidium infection in congenitally athymic (nude) mice

Abstract: Nude (nulnu) BALB/c mice and their white (nul+) littermates were experimentally infected with Cryptosporidium sp. at 6 days of age. In white mice, the infection was transient, but in nude mice a persistent infection developed that was characterized by diarrhea and, occasionally, death. There were villus atrophy and crypt hyperplasia in the small intestine of infected nude and white mice necropsied at 11 days of age. Persistently infected nude mice had, in addition to the above small intestinal lesions, diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(90 citation statements)
references
References 16 publications
4
86
0
Order By: Relevance
“…The host response to infection has been investigated using murine models of infection with C. parvum or C. muris. It is known that the development of immunity is dependent on T-cells (Heine, Moon & Woodmansee 1984); CD4' cells were found to play a crucial role in protection (Ungar et al 199 1, McDonald et al 1994, Harp, Whitmire & Sacco, 1994, Perryman, Mason & Chrisp 1994 while studies in our laboratory indicated that CD8' cells were also involved . Cryptosporidial infection induces a parasite-specific antibody response but depletion of Bcells in mice did not affect the capacity to eliminate C. parvum infection (Taghi-Kilani, Sekla and Hayglass, 1990).…”
Section: Introductionmentioning
confidence: 70%
“…The host response to infection has been investigated using murine models of infection with C. parvum or C. muris. It is known that the development of immunity is dependent on T-cells (Heine, Moon & Woodmansee 1984); CD4' cells were found to play a crucial role in protection (Ungar et al 199 1, McDonald et al 1994, Harp, Whitmire & Sacco, 1994, Perryman, Mason & Chrisp 1994 while studies in our laboratory indicated that CD8' cells were also involved . Cryptosporidial infection induces a parasite-specific antibody response but depletion of Bcells in mice did not affect the capacity to eliminate C. parvum infection (Taghi-Kilani, Sekla and Hayglass, 1990).…”
Section: Introductionmentioning
confidence: 70%
“…The role of cell-mediated immunity in the recovery of mice from Cryptosporidium infection is well documented and the importance of T-lymphocytes, particularly CD4+ T cells has been determined (8,10,16,17,23,24). On the other hand, the significance of CD8+ T cells remain unclear and is probably generally underestimated (25).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of T-cells in immunity to cryptosporidial infection was ®rst shown by Heine et al (1984) who observed that neonatal nude mice developed chronic and eventually fatal C. parvum infections while control mice with an intact thymus developed self-limited infections. In subsequent investigations, a similar increased susceptibility to C. parvum or the rodent gastric parasite Cryptosporidium muris was obtained in adult or neonatal SCID mice (Mead et al 1991, Kuhls et al 1992, McDonald et al 1992, Chen et al 1993a.…”
Section: T-cells and Control Of Infectionmentioning
confidence: 99%